THE INFLUENCE OF MEDIA SET (SCIENCE EDUTAINMENT) USE OF SCIENCE LEARNING OUTCOMES OF BASIC SCHOOL STUDENTS - Winarti, Puji (Faculty of Teacher Training and Education of Undaris, 2017)
Natural Science (IPA) is a subject that is directly related to everyday life. However, when studying in school, students are rarely given a picture that science is a science that is very close to students' lives. This research is motivated by the low science value of students of SDN Gedanganak 01 Ungaran Timur, Semarang Regency due to the presentation of science learning that did not attract students' attention. This study aims to determine the effect of SET media use on science learning outcomes for fourth grade students of SDN Gedang Anak 01 Ungaran Timur, Semarang Regency.This research uses experimental research with quasi experimental design. This study uses the Quasi Exsperimenntal Design Design in the Nonequivalent Group Design form, this design is almost the same as the pretest-posttest control group design, only in the design of the experimental group or the control group not randomly selected. The research population was 32 fourth grade students of Gedanganak 01 Elementary School. After being chosen based on equitable achievement, 16 students were used as the experimental group and 16 students would be used as the control group.Based on the data obtained from the results of the study, prerequisite testing was carried out namely normality test and homogeneity test. From the results of data analysis obtained results that the data is homogeneous and normally distributed. Based on the data analysis, the results of the statistical t test resulted in a value of t count of (5.616)> t table (2.045), so that tcount was in the acceptance area of Ho, then Ha was accepted which stated that there was a significant effect of the use of SET media on learning outcomes of fourth grade students of Public Elementary Schools 01 Gedanganak, Ungaran Timur, Semarang Regency.